2018
DOI: 10.1007/s00170-018-1661-2
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure water-jet-assisted machining of Ti555-3 titanium alloy: investigation of tool wear mechanisms

Abstract: The main objective of this study is to investigate uncoated tungsten carbide tool wear mechanisms for high-pressure waterjet machining of the Ti555-3 titanium alloy. A comparative study has been undertaken (i.e. conventional versus assisted machining) based on numerous experimental tests. These tests have been accompanied by the measurement of the cutting forces and flank wear. It is concluded that the high-pressure water-jet assistance can greatly increase tool life compared to conventional machining, for all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…At a lower pressure of 100bar, cutting forces was reduced by 23% [63]. In another study, Ayed and Geriman [64] reported that the tool life increased by a factor of 8 during HPWJAM of Ti555-3. The cutting speed of up to 75 mm/min gave good machinability but above this speed, the HPWJM was ineffective.…”
Section: Lubricationmentioning
confidence: 99%
“…At a lower pressure of 100bar, cutting forces was reduced by 23% [63]. In another study, Ayed and Geriman [64] reported that the tool life increased by a factor of 8 during HPWJAM of Ti555-3. The cutting speed of up to 75 mm/min gave good machinability but above this speed, the HPWJM was ineffective.…”
Section: Lubricationmentioning
confidence: 99%
“…To solve this problem, scholars at home and abroad have explored how to transform the traditional rock-breaking method and put forward a variety of auxiliary rock-breaking methods. Among them, the highpressure water jet method [8][9] , laser method [10][11] , and highpressure liquid nitrogen jet method [12][13] can reduce the force of disc cutter rock-breaking and improve the efficiency of rockbreaking when assisting TBM disc cutter rock-breaking, but at the same time, there are defects of the technology itself and the limitations of the environment. The high-pressure water jetting method requires high reliability of hydraulic components, and is easy to cause water accumulation, affecting the construction [14] ; The laser method has a small damage range and depth to the rock, and the auxiliary effect is most obvious only when breaking the surface of the rock [15] ; the high-pressure liquid nitrogen jet method has a significant effect on the cold impact fracturing of high-temperature rocks in thermal reservoirs, but the effect is poor in other applications, especially in waterbearing formations [16] .…”
Section: Introductionmentioning
confidence: 99%